Perceptions of online cooperative learning by health science students - Chambi-Mescco, Edith (2023)
Objective: To identify the perceptions of implementing online cooperative learning during the 2021 II academic semesterby first-year students of Universidad Nacional Mayor de San Marcos (UNMSM) School of Medicine. Materials and methods: A descriptive and cross-sectional research design was used in this study. The population consisted of 592 students from the professional schools of Human Medicine, Nursing, Obstetrics, Nutrition and Medical Technology. A random probability sampling was carried out and a sample of 429 students was obtained. The Cooperative Learning Questionnaire with an 8-point Likert scale response format developed by McLeish was used as an instrument for data collection. It is a reliable and valid instrument that was administered online to the sample of students at the end of the course using Google Forms. The quantitative data were analyzed descriptively using IBM SPSS Statistics V22. The descriptive statistics included frequencies, averages and standard deviation. Results: Out of the students in the sample, 65.9 % were females and 34.1 % were males. Most participants had favorableperceptions of online cooperative learning, with averages between 3.77 and 4.53. Favorable perceptions of this methodologywere mainly identified in the dimensions quality of the group interaction process, teaching of interpersonal skills in smallgroups and positive interdependence. Conclusions: The students had favorable perceptions of online cooperative learning because it helped them to improve their social skills, favored their attitude toward group work, allowed them to participate in the sessions with enthusiasm,helped them to improve peer interaction, and promoted the development of their creativity and interpersonal skills. Therefore, its implementation and analysis of achievements in online environments are recommended.